Morphometric variation and species density of Nerita (Neritidae: Gastropoda) in the coastal waters of Ambon Island, Indonesia - Leiwakabessy, Fredy; Latupeirissa, Louvenska Nona (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2023)
Nerita is one of the species with high diversity in the coastal waters of Ambon Island. With this high diversity, the way to assess the length of various Nerita species is through a morphometric study. Meanwhile, density studies are useful for knowing the number of each of these diverse Nerita species. The purpose of this study was to identify the Nerita species to calculate the density and morphometrics. This research was conducted in an intertidal area in two locations, namely Seri and Tawiri villages. The morphometric characteristics of Nerita consist of shell length, shell width, aperture length, spire height, columella length, aperture length, and lip thickness. The density calculation refers to the density formula. The results showed that there were 9 species of Nerita, namely N. polita, N. chamaeleon, N. patula, N. exuvia, N. maxima, N. squamulata, N. albicilla, and N. planospira. N. polita has the highest density value (41.33 ind/m2) while N. patula (0.04 ind/m2) has the lowest density value. Morphometric analysis shows that there are variations in shell size among these species. Shell morphometric variations can be used as a reference for studying the phenetic diversity of Neritaidae in Ambon Island waters